2014
DOI: 10.1371/journal.pone.0087878
|View full text |Cite
|
Sign up to set email alerts
|

Loss of WISP2/CCN5 in Estrogen-Dependent MCF7 Human Breast Cancer Cells Promotes a Stem-Like Cell Phenotype

Abstract: It has been proposed that the epithelial-mesenchymal transition (EMT) in mammary epithelial cells and breast cancer cells generates stem cell features. WISP2 (Wnt-1-induced signaling protein-2) plays an important role in maintenance of the differentiated phenotype of estrogen receptor-positive breast cancer cells and loss of WISP2 is associated with EMT. We now report that loss of WISP2 in MCF7 breast cancer cells can also promote the emergence of a cancer stem-like cell phenotype characterized by high express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…In this case, the protection from CTL‐mediated lysis appeared to be linked with the activation of an autophagic program, which may contribute to promote survival in these cells. A similar impairment of CTL‐mediated lysis was also noted in another model of MCF7 cells undergoing EMT (Akalay et al ., ) wherein silencing of WISP2 (WNT1‐inducible signaling pathway protein 2) coincides with hyperactivity of TGF‐β signaling, EMT, and acquisition of stemness properties (Ferrand et al ., ; Fritah et al ., ). In this instance, the autophagy status did not appear to be involved in the resistant phenotype; however, a disruption of TGF‐β signaling in these cells by treatment with A83‐01, an inhibitor of TGF‐β‐related type I receptors ALK5, ALK4, and ALK7, effectively decreased resistance to CTLs.…”
Section: The Acquisition Of a Mesenchymal Phenotype Is Associated Witmentioning
confidence: 97%
“…In this case, the protection from CTL‐mediated lysis appeared to be linked with the activation of an autophagic program, which may contribute to promote survival in these cells. A similar impairment of CTL‐mediated lysis was also noted in another model of MCF7 cells undergoing EMT (Akalay et al ., ) wherein silencing of WISP2 (WNT1‐inducible signaling pathway protein 2) coincides with hyperactivity of TGF‐β signaling, EMT, and acquisition of stemness properties (Ferrand et al ., ; Fritah et al ., ). In this instance, the autophagy status did not appear to be involved in the resistant phenotype; however, a disruption of TGF‐β signaling in these cells by treatment with A83‐01, an inhibitor of TGF‐β‐related type I receptors ALK5, ALK4, and ALK7, effectively decreased resistance to CTLs.…”
Section: The Acquisition Of a Mesenchymal Phenotype Is Associated Witmentioning
confidence: 97%
“…11,19 To examine directly whether the TGF-b signaling pathway modulated PD-L1 expression, MCF7 sh-WISP2 and MDA-MB-231 cells were treated with two different inhibitors of TGFb signaling. However, as illustrated in Fig.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…We highlighted that WISP2/CCN5 may be a promising therapeutic target and development of WISP2/CCN5 promoter would have a great impact on breast cancer therapy. The relationship between deficiency of WISP2/CCN5 and estrogen dependent MCF-7 has been explored because WISP2/CCN5 is an estrogen response gene in ER-α-positive breast cancer cells, such as MCF-7 cell line, and present studies showed that the estradiol-treatment is able to activate CCN5 transcription [31][32][33] . Therefore, correlation between WISP2/CCN5 and ER, PR and Her-2 still need to be detected in breast cancer.…”
Section: Secondmentioning
confidence: 80%